Modelling surface tension with smoothed particle hydrodynamics in reactive rotational moulding. (2nd September 2015) - Hamidi, A.; Khelladi, S.; Illoul, L.; Shirinbayan, M.; Bakir, F.; Tcharkhtchi, A.
Highlights: SPH surface tension model in 2 and 3D applied to RRM process is proposed. Fitting circle give an accurate computations of surface tension force. The spherical regression gives accurate computations of surface tension. The simulations without surface represent roughness in the internal surface. The simulations undertaken with surface tension give smooth internal surface. Abstract: Reactive Rotational Moulding (RRM) is the best process for producing large hollow plastic parts without weld lines. Constant quality in technical parts requires the process to be mastered by controlling on-line the main physical phenomena. However, the main drawback of RRM is poor control of the process due to the high number of influent parameters. In these conditions, the optimization of the process is quite complex. The aim of this work is to simulate the reactive fluid flow during RRM with Smoothed Particle Hydrodynamics (SPH) solver in two dimensions (2D) and three dimensions (3D) taking into account surface tension force. To implement this force, the interface is tracked explicitly using algorithm developed by Barecasco et al. (2013) and Terissa et al. (2013) and the reconstruction of curve or surface boundary by different interpolation or surface construction technique with Lagrangian interpolation and fitting circle methods in 2D and spherical regression in 3D, respectively.